Electrostimulus-associated PD-L1 expression on cell membrane revealed by immune SERS nanoprobes. Issue 3 (20th January 2022) - Qu, Xiaozhang; Sun, Dan; Cheng, Yuqi; Wang, Jiafeng; Wang, Yan; Xu, Weiqing; Qi, Guohua; Xu, Shuping
Abstract : Smart surface-enhanced Raman scattering nanoprobes are utilized to discriminate and monitor the dynamic expression of PD-L1 under external electrostimulation. Abstract : Programmed cell death ligand 1 (PD-L1) is considered a major immune checkpoint protein that mediates antitumor immune suppression and response. Effectively regulating PD-L1 expression and dynamic monitoring has become a significant challenge in immunotherapy. Herein, we adopted smart surface-enhanced Raman scattering (SERS) nanoprobes to discriminate and monitor the dynamic expression of PD-L1 under external electrostimulation (ES). The PD-L1 expression levels in three cell lines (MCF-7 cells, HeLa cells, and H8 cells) were assessed before and after ES. The results reveal that ES could effectively and rapidly mediate a transformation in the PD-L1 content (or activity) on the cell membrane. Moreover, the molecular profiles of the cell membrane before and after ES were revealed by using the label-free SERS method with the help of immune plasmonic nanoparticles. The cell membrane protein information presented identifiable conformation changes after ES, showing a significant inhibitory effect on the bridge of PD-L1 and its antibody. This study indicates that ES is superior to chemical drugs due to lesser side effects because ES-based regulation does not depend on intracellular signalling pathways. This strategy is versatile and robust for discriminating and monitoring PD-L1 on cell membranes, thus providing potential clinical application value to PD-L1-mediated systems. This study also offers a practical way to assess the molecular profiles of cell membrane proteins in the presence of an external stimulus, which may be applicable to many membrane protein-related studies.